The Effect of Ingratiation and Inspirational Appeals on Customer Trust - Andini Salsabila; Triana Fitriastuti; Sri Wahyuni Riyadi; Windi Anggriyani; Nabilla Azzahra Sayidina (FEB Universitas Mulawarman, 2025)
This study aims to investigate how interpersonal influence tactics employed by salespeople, specifically inspirational appeals and ingratiation, impact customer trust. A quantitative approach was employed by distributing questionnaires to 202 customers in Indonesia who had interacted with salespeople to obtain product information or recommendations. Multiple linear regression analysis was conducted to assess the impact of each tactic on customer trust. The results show that inspirational appeal has a negative and significant effect on customer trust, indicating that emotionally driven or value-oriented messages delivered by salespeople can reduce customer trust, possibly because they are misaligned with customer expectations or needs. In contrast, ingratiation has a negative but not statistically significant effect on customer trust, suggesting that compliments, flattery, or excessive and insincere attempts to win customers’ favor are insufficient to influence their level of trust. These findings suggest that interpersonal influence tactics must be matched to customer characteristics, and not all approaches are equally effective in building trust.